2020
DOI: 10.1111/ejh.13363
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of venous thromboembolism prophylaxis among hospitalized patients with liver disease

Abstract: Introduction Patients with liver disease are at risk of venous thromboembolism (VTE); however, little is understood regarding the safety and efficacy of VTE prophylaxis in patients with cirrhosis. We examined the application of a VTE risk assessment model in VTE prophylaxis decision‐making in a closed cohort of hospitalized patients with liver disease. Methods Sequential patients admitted to an inpatient hepatology service at a tertiary care center were evaluated for need for VTE prophylaxis. Risk assessment b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…There were 5 retrospective cohort studies reporting VTE events in hospitalized patients with cirrhosis receiving prophylactic anticoagulation. 18,[76][77][78][79] VTE events were defined as deep vein thrombosis (DVT) or pulmonary embolism (PE) or PVT and presented as composite end points in most studies, irrespective of symptom presence. The retrospective nature of the studies without systematic screening for VTE limits robust interpretation to support clinical guidance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 5 retrospective cohort studies reporting VTE events in hospitalized patients with cirrhosis receiving prophylactic anticoagulation. 18,[76][77][78][79] VTE events were defined as deep vein thrombosis (DVT) or pulmonary embolism (PE) or PVT and presented as composite end points in most studies, irrespective of symptom presence. The retrospective nature of the studies without systematic screening for VTE limits robust interpretation to support clinical guidance.…”
Section: Resultsmentioning
confidence: 99%
“…There were 3 retrospective cohort studies reporting bleeding events in those with vs without prophylactic anticoagulation during hospitalization. 18,78,79 All bleeding events was defined as the overall number of major and minor bleeds reported in the study. Major bleeding (reported in 2 studies) was defined per the International Society on Thrombosis and Haemostasis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite clear evidence of increased risk for VTE, hospitalized patients with cirrhosis have not been typically included in most studies of thromboprophylaxis with anticoagulation, and no RCTs were found comparing outcomes of prophylactic anticoagulation in patients with cirrhosis. Review of the literature by the TR identified only 5 retrospective studies [57][58][59][60][61] that examined the risk of thrombotic events in patients with cirrhosis. Given the observational and retrospective design, without welldefined outcomes (all thrombotic events, ie, deep venous thrombosis, pulmonary embolism, and PVT, were considered together) and lack of systematic screening for VTE, the TR team explored data from well-done RCTs in the general medical population, as well as previously published guidelines.…”
Section: Summary Of the Evidencementioning
confidence: 99%